The Security media and its policy in the face of terrorist activities: An analytical study of Iraq's media policy - the Security Media Cell as a sample - Abdel Hamid, Hanaa Abdul Hamid Ibrahim; AlAmiri, Rasool Mutlaq Mohammed (Al-Adab Journal, 2023)
This study aims to provide an analysis of the effectiveness of the national media policy for the Iraqi security institutions, as an entity responsible for achieving security awareness in the country, and its role in preventing terrorist crimes, this study aims to shed light on the concept of security media, the beginnings of the concept, its starting points, and the challenges that limit its effectiveness and roles in confronting terrorist activities. Where this study is divided into three main sections, reviews in its first part the basic elements of the research (the problem of the study, the importance of the study, the objectives of the study), while the second topic came as an extension of the most important concepts and scientific terms that explain the variables of the study, while the last topic dealt with: the objectives of security media Its functions and tasks, the problems facing the security media, and the explanation of the most important mechanisms of the security media and its role in confronting terrorist activities .